2006
DOI: 10.1002/j.2050-0416.2006.tb00718.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Inoculum Level on Fermentation and Flavour Compounds of White Wines Made from cv. Emir

Abstract: In this study, the influence of the addition of a commercial wine yeast (Saccharomyces cerevisiae) at inocula of 1 × 104 to 1 × 107 cells/ml in Emir must was investigated with a focus on yeast growth, fermentation rate, ethyl alcohol and flavour compound formation. Spontaneous fermentation without inoculation was also performed. Higher peak counts were observed with higher amounts of S. cerevisiae yeast. Addition of various amounts of yeast led to the earlier disappearance of non‐Saccharomyces yeasts. The ferm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 27 publications
3
33
0
7
Order By: Relevance
“…Overall, we observed that increasing inoculum size led to higher concentration of alcohols. Our results are in agreement with those of Mateo et al (2001), Erten et al (2006) and Verbelen et al (2009a, b), who studied the influence of yeast inoculum size on the fermentation performance and the volatile compound formation of wine and beer. The concentration of alcohols was below 300 mg/L in all of our meads, representing values considered desirable for increasing the complexity of wines (Ugliano and Henschke, 2009;Mateo et al, 2001).…”
Section: Effect Of Pitching Rate On Mead Aroma Profilesupporting
confidence: 83%
See 2 more Smart Citations
“…Overall, we observed that increasing inoculum size led to higher concentration of alcohols. Our results are in agreement with those of Mateo et al (2001), Erten et al (2006) and Verbelen et al (2009a, b), who studied the influence of yeast inoculum size on the fermentation performance and the volatile compound formation of wine and beer. The concentration of alcohols was below 300 mg/L in all of our meads, representing values considered desirable for increasing the complexity of wines (Ugliano and Henschke, 2009;Mateo et al, 2001).…”
Section: Effect Of Pitching Rate On Mead Aroma Profilesupporting
confidence: 83%
“…No differences in 3-methyl-1-butanol were observed in meads fermented at different pitching rates by the strain ICV D47, whereas a higher concentration of this alcohol was detected only at the lowest pitching rate (1.5 Â 10 5 CFUs/mL) with the strain QA23. Different results were obtained by Mateo et al (2001), Erten et al (2006), Verbelen et al (2008) and Verbelen et al (2009a), who indicated a direct dependence of the concentration of that compound on inoculum size. Esters represented the most diverse group with ten compounds quantified.…”
Section: Effect Of Pitching Rate On Mead Aroma Profilementioning
confidence: 92%
See 1 more Smart Citation
“…The β-damascenone in the fractions was analyzed by GC-MS. As references, ethanol, isobutanol, and furfural were also analyzed. Isobutanol is one of the higher alcohols and higher alcohols are the most important group of volatile compounds in liquor 5,8 . Higher alcohols are formed by the Ehrlich pathway in yeast 11 .…”
Section: Formation Of β-Damascenone During Distillationmentioning
confidence: 99%
“…cerevisiae inoculadas en distintos porcentajes tienen sobre la supervivencia de las levaduras no-Saccharomyces, y la relación con la concentración de determinados metabolitos (Erten et al, 2006 www.lallemandwine.com). Desde el punto de vista de la aplicabilidad en bodega, resultaría más atractivo un cultivo iniciador con los porcentajes mínimos de levadura no-Saccharomyces que permitieran obtener el efecto deseado y a la vez modular la supervivencia de la levadura.…”
Section: Implantación De Los Cultivos Iniciadores Mixtosunclassified